Measurement of the WZ production cross section in pp collisions at s=13 TeV - Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Erö, J.; Flechl, M.; Friedl, M.; et al. (My University, 2017)
The WZ production cross section in proton–proton collisions at s=13 TeV is measured with the CMS experiment at the LHC using a data sample corresponding to an integrated luminosity of 2.3 fb?1. The measurement is performed in the leptonic decay modes WZ???????, where ?,??=e,?. The measured cross section for the range 60<m????<120 GeV is ?(pp?WZ)=39.9±3.2(stat) (syst)?3.1+2.9±0.4(theo)±1.3(lumi) pb, consistent with the standard model prediction. © 2017 The Author(s)
Citation: Khachatryan, V., Sirunyan, A. M., Tumasyan, A., Adam, W., Asilar, E., Bergauer, T., . . . Woods, N. (2017). Measurement of the WZ production cross section in pp collisions at s=13 TeV. Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 766, 268-290. doi:10.1016/j.physletb.2017.01.011
Keywords: Cms; Electroweak; Physics